A new species from the Turkey, Atriplex sukhorukovii (Chenopodiaceae) - Başköse İsa; Yaprak, Ahmet Emre (Phytotaxa, 2018)
As part of the ongoing taxonomic revision of Atriplex (Chenopodiaceae) in Turkey, the occurrence of A. pungens was revealed to be not confirmed and all the specimens previously referred to this species are proposed here as a new species, i.e. A. sukhorukovii sp. nov. It close to A. davisii but differs in habitus, leaves shape and size, inflorescence, seed structure, and habitat preference. Diagnosis, description, illustrations, and original drawings of A. sukhorukovii as well as its distribution map are given. A diagnostic key of the Turkish species beloning to Sect. Teutliopsis, and chromosome numbers (diploidy, 2x=18) are also provided.